Oxidative Phosphorylation Impairment by DDT and DDE - Elmore, Sarah E.; La Merrill, Michele A. (Frontiers in Endocrinology, 2019)
There is increasing evidence supporting the characterization of the pesticide DDT and its metabolite, DDE, as obesogens and metabolic disruptors. Elucidating the mechanism is critical to understanding whether the association of DDT and DDE with obesity and diabetes is in fact causal. One area of research investigating the etiology of metabolic diseases is mitochondrial toxicity. Several studies have found associations between mitochondrial defects and insulin resistance, cellular respiration, substrate utilization, and energy expenditure. Although the mitotoxicity of DDT and DDE was established 20 to 40 years ago, it was not viewed in the light of the diseases faced today, therefore, it is prudent to reexamine the mitotoxicity literature for mechanistic support of DDT and DDE as causal contributors to obesity and diabetes, as well as associated diseases such as cancer and Alzheimer’s disease. This review aims to focus on studies investigating the effect of DDT or DDE on mammalian mitochondrial oxidative phosphorylation. We illustrate that both DDT and DDE impair the electron transport chain (ETC) and oxidative phosphorylation. We conclude that there is reasonable data to suggest that DDT and DDE target specific complexes and processes within the mitochondria, and that these insults could in turn contribute to the role of DDT and DDE in mitochondria-associated diseases.